The Relationship of Pregnant Women's Knowledge about the Provision of Tetanus Toxoid Immunization to Pregnancy in Pmb Tri Lasiyanti Kelurahan Jatimakmur Pondok Gede, Bekasi City 2022 - Tri Lasiyanti; Sukarni Sukarni (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The purpose of this study was to determine the effect of the level of knowledge of pregnant women about giving tetanus toxoid immunization during pregnancy at PMB Tri Lasiyanti, Jatimakmur Village, Pondok Gede, Bekasi City in 2022. Methods:  This study uses an analytical survey with a cross-sectional approach. The sample used in this study amounted to 49 pregnant women using quota sampling that met the inclusion and exclusion criteria. Results:  Based on the results of the chi-square test, the p-value of 0.001 shows that there is a relationship between the two variables, meaning that the mother's level of knowledge can affect the administration of tetanus toxoid immunization at PMB Tri Lasiyanti, Jatimakmur Village, Pondok Gede, Bekasi City 2022. Conclusion:  From a study conducted in 2 months under the title "Level of Knowledge of Pregnant Women About Giving Tetanus Toxoid Immunization Against Pregnancy at PMB Tri Lasiyanti, Jatimakmur Village, Pondok Gede, Bekasi City 2022", based on the independent and dependent variables from the results carried out using data analysis namely univariate and bivariate analysis where both have the same result that is related, with a p-value of 0.001. For further researchers, it can be used as reading material and can be used as basic data as a comparison for further research with variables and a deeper level of analysis about the level of mother's knowledge about tetanus toxoid immunization.